ATYPICAL UNILATERAL FEMORAL FRACTURE IN A POSTMENOPAUSAL FEMALE AFTER TREATMENT OF BISPHOSPHONATES AND DENOSUMAB: A CASE REPORT - Tolentino, Kurt Bryan; Yu, Quennie Bien Bien; Pestaño, Camille; Cabral , Monica Therese (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE The incidence of atypical femoral fractures (AFF) and bisphosphonates with denosumab usage have not been established, although individually uncommon, yielding an incidence of 0.90 and 7.8 per 100,000 patient years, respectively. This discusses an 81-year-old female, known osteoporotic and diabetic, previously on alendronate for 10 years, ibandronate from 2020-2022, and 2 doses of denosumab (November 2022, May 2023), complaining of a 4-month history of a right thigh pain without any history of trauma or fall and improvement from physical rehabilitation. Previous X-rays did not reveal any fractures. On the day of the consult, she complained of a sudden onset of severe right thigh pain. Repeat imaging studies revealed a complete, transverse, noncomminuted fracture of the proximal femoral diaphysis. She underwent closed reduction, and intramedullary nailing with the application of autologous bone graft and was sent home well. The link between AFF and the subsequent use of bisphosphonates and denosumab should be further established in high-risk patients.